Endothelium and arterial hypertension - Cobos S, Leonardo (2014)
Role of endothelial function in cardiovascular health and its relation with arterial hypertension has been demonstrated. Some studies show that endothelial dysfunction may produce arterial hypertension but other studies find that arterial hypertension per se produces endothelial damage. Due to the fact of various clinical conditions associated to endothelial dysfunction it is of great interest protection of the endothelium.